2021
DOI: 10.1080/09575146.2021.1889992
|View full text |Cite
|
Sign up to set email alerts
|

Understanding holistic and unique childhoods: knowledge generation in the early years with autistic children, families and practitioners

Abstract: Understanding holistic and unique childhoods: knowledge generation in the early years with autistic children, families and practitioners

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Content : For the ‘I am …’ and ‘Who we are …’ Digital Stories we are following the analysis method summarised in Parsons et al, 2022b) which involved creating a ‘transcript of action’ for each Story that describes what is seen as well as what is said and using our existing ‘I am …’ Digital Story Framework (Parsons et al, 2021) to categorise this information. Once the videos are transcribed, it is possible to collate and represent the data in different ways; for example, Parsons et al, (2021) used word clouds to show the verbs that were used to describe children’s skills and activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Content : For the ‘I am …’ and ‘Who we are …’ Digital Stories we are following the analysis method summarised in Parsons et al, 2022b) which involved creating a ‘transcript of action’ for each Story that describes what is seen as well as what is said and using our existing ‘I am …’ Digital Story Framework (Parsons et al, 2021) to categorise this information. Once the videos are transcribed, it is possible to collate and represent the data in different ways; for example, Parsons et al, (2021) used word clouds to show the verbs that were used to describe children’s skills and activities.…”
Section: Discussionmentioning
confidence: 99%
“…'I think the Digital Stories are amazing, I loved them so much … I think it would be amazing for schools and professionals to watch prior to the child's start … There is too much pressure on the parents to have to try to explain what their child is like, because you can't explain in words a person, … I don't like the pressure of explaining what my son is like myself, because I worry that I'm not portraying accurately enough … -Anita, Oscar's Mum (https://autismtransitions.org/thoughts-on-digital-stories/) Essential to the success of this research methodology was its co-construction with the children, families, and practitioners in early years practice (Parsons et al, 2021(Parsons et al, , 2022a(Parsons et al, , 2022b. Fundamental to this approach is an epistemological understanding that for research methods aimed at influencing practice, the generation of new knowledge must appropriately recognise, respect, and reflect the individual and local contexts of inquiry (Thomas, 2012), as well as the expertise or craft knowledge of practitioners (Hammersley, 2005;Nind, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes providing "childled special place tours" (Green, 2013, p. 13), joining in "walking interviews" around their schools (Green, 2013), or taking photographs of aspects of school life that they associate with "friendships, relationships and wellbeing" (Allan & Jorgerson, 2021, p. 332), illustrating "what it is to be 'included' or 'excluded'" (Dunne et al, 2018, p. 22). Shifting from their traditional positions as the object of others' gaze to being behind the camera, enables child researchers, quite literally, a different point of view (Parsons et al, 2021). Involving children in asking "Whose space is this?"…”
Section: What Space Do I Rightfully Occupy?mentioning
confidence: 99%
“…The review also revealed the ethical, social and experiential forces influencing children's agency and their voice in research (Mayne and Howitt, 2015;Halpenny, 2021). Building on these findings, the research team developed specific/tailored protocols for engaging with Dalkilic, 2020;García-Carrión et al, 2020;Parsons et al, 2021), as well as the benefits of adopting co-constructed forms of communication to fully capture children's perspectives (Blaisdell et al, 2021). Therefore, as part of the larger project, children contributed their perspectives about their experiences in education and care settings, including the qualities of the educators with whom they spent their time.…”
Section: An Exemplar Of Children's Contribution In the Research Desig...mentioning
confidence: 99%